Discursive use of modality in RT’s coverage of Russia’s war on Ukraine - Ihor Matseliukh (East European Journal of Psycholinguistics)
The current article looks into various types of modality use through the prism of critical discourse analysis strategies in the coverage of Russia’s war against Ukraine by the international news provider RT. It aims to uncover how discursive practices, in the name of the Russian state ideology, govern the choice of modality means and explain their dependence on and relevance to the news stories, actors, circumstances within the broader field of representation. The corpus for this article was compiled on RT’s website within one week from July 17th to 24th, 2024, almost two and a half years into Russia’s full-scale invasion of Ukraine. It consists of 93 news stories of Ukraine related content comprising 41,418 words and containing different types of modality, occasionally with references to alternative sources, in order to assess and uncover the biased ideological practices on the RT channel. Epistemic modality with its divisional kinds along with the modality of negativity is uncovered; as well as deontic modality, which reflects the ideology of RT‘s propagandistic narratives centered around Western states positioned against Russia’s friendly nations. Conflicting tendencies of factive and emotional reporting are discerned. Quantitative results have been arrived at resorting to both the percentage format and a Mann-Whitney U test, taking into account a similar corpus on the Venezuela crisis of 2019-2020. Modality implementation and distribution provides insight into the RT’s propaganda techniques. The article redirects critical discourse analysis towards news consumption, raising awareness of the readership and enhancing news literacy.